STUDIES ON OZONE AND AUTOLOGOUS PLASMA INTRA-UTERINE THERAPY IN INFECTIOUS REPEAT BREEDER COWS - AITALWAD, R S; SAWALE, A G; MARKANDEYA, N M (The Indian Journal of Animal Reproduction, 2021)
The study was undertaken to evaluate the therapeutic efficacy of Ozone and Autologous plasma in 40 infectiousrepeat breeder cows. The animals were divided in 2 different groups viz. Group-I 20 and Group-II 20 treated withOzone @55μg/ml in 60ml distilled water and Autologous plasma @ 30ml in intrauterine route, respectively. Thediagnosis was confirmed by estimation of pH, PMN cell count, White Side Test and Spinnbarkeit test, which indicated93.00% cows having alkaline pH, PMN cell count >5% and all cases positive for White Side Test. It was observed thatpH of CVM in infectious cows before treatment was 8.00±0.07 and 8.13±0.08 which was reduced after treatment7.32±0.07 and 7.49±0.08, while PMN cells before treatment revealed as 9.35±0.37 and 9.80±0.44 which was changedto 4.90±0.40 and 4.80±0.65 after treatment and Spinnbarkeit value before treatment was 9.00±0.32 and 9.15±0.27changed to 15.15±0.59 and 14.95±0.61 after treatment under Groups-I and II, respectively. Recovery rate after treatmentwere found as 75.00 and 65.00 per cent, respectively. The conception rate was found as 68.42 and 55.00 per cent incows in Group-I and II, respectively. On conclusion, cows treated with Ozone showed higher recovery rate.
Keywords: Ozone; Autologous plasma; Intra-uterine therapy; Recovery rate; Repeat Breeder cows